2013
DOI: 10.1007/978-1-4614-6130-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Exerts Robust Protection Against Hypoxia and Oxygen/Glucose Deprivation in Human Neuroblastoma Cell Culture

Abstract: Stroke is one of the leading causes of mortality and disability worldwide. There is no effective treatment for stroke despite extensive research. Taurine is a free amino acid which is present at high concentrations in a range of organs including the brain, heart, and retina in mammalian systems. It had been shown that taurine can significantly increase cell survival under stroke conditions using both in vivo and in vitro models. Recently, we have found that several agents including granulocyte colony-stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It has a multiple of neuroprotective mechanisms in the CNS such as: regulating cellular osmolarity [243,244], an anti-oxidant [65,66], neuromodulator of GABAergic transmission [85,245,246], maintaining calcium homeostasis [59,60,61,62,63], inhibiting glutamate excitotoxicity [59,69,133], attenuating endoplasmic reticulum stress [73,190,247], modulating the mitochondrial pore permeability [155] downregulating a range of pro-apoptotic proteins while upregulating anti-apoptotic proteins [70,176,179,248] and downregulating inflammatory mediators [217]. In ischemic stroke, a pathological brain condition, taurine is released in the extracellular space resulting in a decrease in the concentration of intracellular taurine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a multiple of neuroprotective mechanisms in the CNS such as: regulating cellular osmolarity [243,244], an anti-oxidant [65,66], neuromodulator of GABAergic transmission [85,245,246], maintaining calcium homeostasis [59,60,61,62,63], inhibiting glutamate excitotoxicity [59,69,133], attenuating endoplasmic reticulum stress [73,190,247], modulating the mitochondrial pore permeability [155] downregulating a range of pro-apoptotic proteins while upregulating anti-apoptotic proteins [70,176,179,248] and downregulating inflammatory mediators [217]. In ischemic stroke, a pathological brain condition, taurine is released in the extracellular space resulting in a decrease in the concentration of intracellular taurine.…”
Section: Discussionmentioning
confidence: 99%
“…Within the mitochondrion, taurine may also attenuates excessive ROS generated in ischemic stroke [65,212]. Taurine protects the endoplasmic reticulum from being stress, evidential by the reduction of ER stress markers such as CHOP and caspase-12 in taurine-treated experimental models [73,190,247]. …”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma (NB) cell cultures are widely used to study neuritogenic and neuroprotective properties of bioactive substances [15,16]. Usually there are several percent of spontaneously differentiating cells in NB C-1300 culture, and the number of differentiated cells increases after prolonged cultivation or cultivation in media with low serum content [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…The higher levels of taurine found in hypoxic cells compared with normoxic ones is in-line with observations in glioblastoma cell lines [ 51 ] and might be an adaptation mechanism for cells to survive better in hypoxic conditions. Indeed, it has been shown that taurine can protect human neuroblastoma cells in culture [ 53 ] and may exert a protective function against hypoxia/reoxygenation by reducing the endoplasmic reticulum stress [ 54 ]. In addition, taurine administered during hypoxia can reduce the cell damage due to O 2 deficiency [ 55 ].…”
Section: Discussionmentioning
confidence: 99%